Child-Care Costs and Family Labor Supply - Blau, David M.; Robins, Philip K. (The Review of Economics and Statistics, 1988)
This paper presents a theoretical and empirical analysis of the effects of child care costs on family labor supply and the demand for market child care. The model is a framework for cross-section estimation of the effects of child care costs on labor supply and child care use. It applies to households having young children requiring continuous care and in which both the mother and 1 other potential child care provider are present. The 3 potential sources of child care are the mother the potential informal provider and the market. Using data from the 1980 baseline household survey of the Employment Opportunity Pilot Projects this empirical analysis uses a subsample of 6170 households in which there is a married woman under age 45 with her spouse present at the time of the survey at least 1 child under age 14 and nonmissing data on key variables. Results show that 1) higher market child care costs discourage women from working even when an informal source of care is available indicating that such informal care is an imperfect substitute for market care; 2) a higher wage rate for the mother encourages her to work thus a higher wage rate increases the probability of using market child care; 3) the number of children requiring care has a negative impact on the probability of the women working with the largest impact caused by younger children; 4) nonwage income has a negative impact on the probability of the woman working; and 5) black women are more likely to work than whites and are statistically more likely than whites to use market child care if they do work. This family labor supply model predicts that the cost of market child care will affect household decisions on labor supply and child care use. Estimates of a qualitative choice model provide strong confirmation that child care costs affect such decisions. The responsiveness of the labor supply of mothers to child care costs demonstrated in this study indicate that such subsidies do have their intended effect of encouraging labor supply. The fact that a large proportion of current child care subsidies benefit primarily middle and upper income families via the income tax credit suggests that the labor supply effets of such subsidies may in practice be stronger for less needy families than for low income families. Employer-subsidized child care may become an increasingly popular tool for attracting mothers into the labor force.